2017
DOI: 10.1186/s12906-017-1903-0
|View full text |Cite
|
Sign up to set email alerts
|

[6]-Gingerol, from Zingiber officinale, potentiates GLP-1 mediated glucose-stimulated insulin secretion pathway in pancreatic β-cells and increases RAB8/RAB10-regulated membrane presentation of GLUT4 transporters in skeletal muscle to improve hyperglycemia in Leprdb/db type 2 diabetic mice

Abstract: Background[6]-Gingerol, a major component of Zingiber officinale, was previously reported to ameliorate hyperglycemia in type 2 diabetic mice. Endocrine signaling is involved in insulin secretion and is perturbed in db/db Type-2 diabetic mice. [6]-Gingerol was reported to restore the disrupted endocrine signaling in rodents. In this current study on Leprdb/db diabetic mice, we investigated the involvement of endocrine pathway in the insulin secretagogue activity of [6]-Gingerol and the mechanism(s) through whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 46 publications
1
60
0
Order By: Relevance
“…In addition, Streptozotocin-induced diabetic rats treated orally with 500 mg kg −1 of ginger extract daily had lower glycated hemoglobin (HbA1 C ) compared to a control group [48]. In fact, several studies have introduced the antihyperglycemic effect of dietary ginger on blood glucose [49,50,51]. On the other hand, studies have shown that, in diabetic conditions, the amelioration of blood glucose enhances testosterone production [52,53].…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…In addition, Streptozotocin-induced diabetic rats treated orally with 500 mg kg −1 of ginger extract daily had lower glycated hemoglobin (HbA1 C ) compared to a control group [48]. In fact, several studies have introduced the antihyperglycemic effect of dietary ginger on blood glucose [49,50,51]. On the other hand, studies have shown that, in diabetic conditions, the amelioration of blood glucose enhances testosterone production [52,53].…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Hu et al [101] studied the effects of ginger (Zingiber officinale Roscoe, Zingiberaceae) on gastric motility and emptying, abdominal symptoms, and hormones that influence motility in dyspepsia, including GLP-1 values, and they observed that the serum concentration of this incretin was modified. In the same line, Samad et al [102] recently reported that GLP-1 mediates the insulinotropic activity of [6]-gingerol (▶ Fig. 7), the major component of ginger.…”
Section: Plantmentioning
confidence: 71%
“… 5 (6)-gingerol increases glucose uptake in skeletal muscle by increasing GLUT4 membrane expression. 24 …”
Section: Discussionmentioning
confidence: 99%